How does bark contribution to postural control change during tree ontogeny? A study of six Amazonian tree species. (13th February 2020) - Lehnebach, Romain; Alméras, Tancrède; Clair, Bruno
Abstract: Recent works revealed that bark is able to produce mechanical stress to control the orientation of young tilted stems. Here we report how the potential performance of this function changes with stem size in six Amazonian species with contrasted bark anatomy. The potential performance of the mechanism depends both on the magnitude of bark stress and the relative thickness of the bark. We measured bark longitudinal residual strain and density, and the allometric relationship between bark thickness and stem radius over a gradient of tree sizes. Constant tensile stress was found in species that rely on bark for the control of stem orientation in young stages. Other species had increasing compressive stress, associated with increasing density attributed to the development of sclereids. Compressive stress was also associated with low relative bark thickness. The relative thickness of bark decreased with size in all species, suggesting that a reorientation mechanism based on bark progressively performs less well as the tree grows. However, greater relative thickness was observed in species with more tensile stress, thereby evidencing that this reduction in performance is mitigated in species that rely on bark for reorientation. Abstract : During ontogeny, species that rely on bark for posture control maintain thick bark and constant tensile stress, while other species have relatively thinner bark and increasing compressive stress.